2020
DOI: 10.1038/s41598-020-71760-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E is necessary for zebrafish nervous system development

Abstract: Vitamin E (VitE) deficiency results in embryonic lethality. Knockdown of the gene ttpa encoding for the VitE regulatory protein [α-tocopherol transfer protein (α-TTP)] in zebrafish embryos causes death within 24 h post-fertilization (hpf). To test the hypothesis that VitE, not just α-TTP, is necessary for nervous system development, adult 5D strain zebrafish, fed either VitE sufficient (E+) or deficient (E−) diets, were spawned to obtain E+ and E− embryos, which were subjected to RNA in situ hybridization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…Morphological deformities including yolk sac and pericardial edemas, bent axes, and apparent developmental delays generally occur after 24 hpf in E– embryos as previously reported [ 12 ]. To evaluate gene expression differences based on VitE status alone and not phenotypic changes, only embryos identified as morphologically normal were used.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Morphological deformities including yolk sac and pericardial edemas, bent axes, and apparent developmental delays generally occur after 24 hpf in E– embryos as previously reported [ 12 ]. To evaluate gene expression differences based on VitE status alone and not phenotypic changes, only embryos identified as morphologically normal were used.…”
Section: Resultssupporting
confidence: 60%
“…The outcomes of this study show that VitE deficiency disrupts numerous gene expression networks, including energy metabolism, oxidoreductase activity, intra- and intercellular signaling, and developmental transcriptional regulation, during critical developmental windows in zebrafish embryos. We previously identified that VitE deficiency prevents proper neural crest cell migration and impairs midbrain–hindbrain development [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These latter studies suggested that choline, betaine and the methionine cycle were dysregulated by inadequate VitE protection during embryogenesis. The dysregulation of these pathways in E− embryos causes abnormal nervous system formation, especially the midbrain-hindbrain boundary, spinal cord and dorsal root ganglia [ 14 ]. Thus, we raise the question “why is a water-soluble methyl donor dysregulated during VitE deficiency?” We hypothesize that an increased requirement for GSH during the increased lipid peroxidation observed in E− embryos drives a complex mechanism of overlapping biochemical pathways needed to maintain thiol homeostasis that is dependent on betaine and methyl group donation.…”
Section: Introductionmentioning
confidence: 99%